Identification of fruit related microRNAs in cucumber (Cucumis sativus L.) using high‐throughput sequencing technology. Issue 6 (December 2014) - Ye, Xueling; Song, Tiefeng; Liu, Chang; Feng, Hui; Liu, Zhiyong
<x xml:space="preserve">Abstract</x> MicroRNAs (miRNAs) are approximately 21 nt noncoding RNAs that influence the phenotypes of different species through the post‐transcriptional regulation of gene expression. Although many miRNAs have been identified in a few model plants, less is known about miRNAs specific to cucumber (Cucumis sativus L.). In this study, two libraries of cucumber RNA, one based on fruit samples and another based on mixed samples from leaves, stems, and roots, were prepared for deep‐sequencing. A total of 110 sequences were matched to known miRNAs in 47 families, while 56 sequences in 46 families are newly identified in cucumber. Of these, 77 known and 44 new miRNAs were differentially expressed, with a fold‐change of at least 2 and p‐value < 0.05. In addition, we predicted the potential targets of known and new miRNAs. The identification and characterization of known and new miRNAs will enable us to better understand the role of these miRNAs in the formation of cucumber fruit.